Low anti‐HBc levels are associated with lower risk of virological relapse after nucleos(t)ide analogue cessation in HBe antigen‐negative patients. (5th October 2022) - Ohlendorf, Valerie; Wübbolding, Maximilian; Gineste, Paul; Höner Zu Siederdissen, Christoph; Bremer, Birgit; Wedemeyer, Heiner; Cornberg, Markus; Maasoumy, Benjamin
Abstract: Background and Aims: Low anti‐HBc serum levels at the time of therapy cessation were linked to a higher relapse risk in predominantly HBeAg‐positive cohorts. We investigated the association of anti‐HBc levels with relapse in HBeAg‐negative patients. Methods: Serum levels of anti‐HBc, HBsAg and HBcrAg were determined in 136 HBeAg‐negative patients, participating in a vaccination trial (ABX‐203, NCT02249988), before treatment cessation or vaccination. Importantly, vaccination showed no impact on relapse. The correlation between the biomarkers and their predictive value for relapse (HBV DNA >2000 IU/ml ± ALT >2xULN) was investigated. Results: After therapy cessation 50% ( N = 68) of patients relapsed. Median anti‐HBc prior to treatment stop was significantly higher among relapsers compared to off‐treatment responders (520 IU/ml vs. 330 IU/mL, p = .0098). The optimal anti‐HBc cut‐off to predict relapse was 325 IU/ml according to the Youden‐Index. About 35% of patients with anti‐HBc level < 325 IU/ml versus 60% of those with values ≥325 IU/mL relapsed ( p = .0103; sensitivity 50%, specificity 75%). Combining the optimal cut‐offs of HBsAg (>3008 IU/mL) or HBcrAg (≥1790 U/ml) with anti‐HBc increased the proportion of patients with relapse to 80% ( p < .0001) and 74% ( p = .0006), respectively. Conclusion: In contrast to predominantly HBeAg‐positive cohorts, in our cohort of HBeAg‐negative patients lower anti‐HBc levels are associated with a significantly lower relapse risk after nucleos(t)ide analogue cessation. The vast majority of included patients were either genotype B or C and the applicability to other genotypes has to be further evaluated. However, anti‐HBc level as an indicator of the host response might be prospectively further explored for prediction models.